KAJIAN LAMA REAKSI TERHADAP RENDEMEN MASSA DAN AKTIVITAS ANTIMIKROBA PRODUK GLISEROLISIS - Havita Dwi Anggasari; Murhadi Murhadi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
The study was conducted to determine the effect of glycerolysis reaction time (48, 72, 96, 120 and 144 hours) on yield and antimicrobial activity of glycerolysis products from palm kernel oil (PKO) using rice bran as biocatalyst. The result showed that fractionation of glycerolysis products at all reaction time levels were yielding fraction A (61,8%) that higher than fraction B (21,8%) and fraction C (16,3%). Generally, all fractions (A, B and C) from all treatments have antimicrobial activity. Average of inhibition zone diameter (d) values of fraction C for all reaction time levels against S. aureus, B. subtilis, E. coli, and S. cerevisiae, i.e. 7,66; 6,81; 1,33; and 9,09 mm/6 mg fraction, respectively. Antimicrobial activity of fraction C was higher than fraction A and B, especially against S. aureus, B. subtilis, and S. cerevisiae at 72 and 96 h. of reaction times. Escherichia coli is more resistant bacteria to all fractions than another microbes in this study. All fractions from all reaction time levels be able to reduce of total mold (A. orizae) colony with each average percentage of 79,6 (fraction A); 81,0 (fraction B); and 78,2% (fraction C). Keywords: Glycerolysis, PKO, fraction, antimicrobial activity, resistant.